MACULAR CHOROIDAL VOLUME CHANGES AFTER INTRAVITREAL BEVACIZUMAB FOR EXUDATIVE AGE-RELATED MACULAR DEGENERATION. Issue 12 (December 2017) - Palkovits, Stefan; Seidel, Gerald; Pertl, Laura; Malle, Eva M.; Hausberger, Silke; Makk, Johanna; Singer, Christoph; Osterholt, Julia; Herzog, Sereina A.; Haas, Anton; Weger, Martin
Abstract : Purpose: To evaluate the effect of intravitreal bevacizumab on the macular choroidal volume and the subfoveal choroidal thickness in treatment naïve eyes with exudative age-related macular degeneration. Methods: The macular choroidal volume and the subfoveal choroidal thickness were measured using enhanced depth imaging optical coherence tomography. After a screening examination, each patient received 3 monthly intravitreal injections of 1.25 mg bevacizumab. One month after the third injection was a final assessment. Results: Forty-seven patients with a mean age of 80 ± 6.4 years were included. The macular choroidal volume decreased significantly from median 4.1 mm 3 (interquartile range 3.4–5.9) to median 3.9 mm 3 (interquartile range 3.1–5.6) between the baseline and final examination (difference −0.46 mm 3, 95% confidence interval: −0.57 to 0.35, P < 0.001). Similarly, subfoveal choroidal thickness had decreased from 157.0 μ m (interquartile range 116.0–244.5) at baseline to 139.0 μ m (interquartile range 102.5–212.0) at the final examination ( P < 0.001). Both parameters macular choroidal volume at baseline and subfoveal choroidal thickness at baseline were not associated with the response to treatment. Conclusion: The macular choroidal volume and the subfoveal choroidal thickness decreased significantly after 3 monthly bevacizumab injections for exudative age-related macular degeneration. Abstract : Supplemental Digital Content is Available in the Text.The present study evaluated the effect of three consecutive intravitreal bevacizumab injections on the choroidal volume and the choroidal thickness in patients with exudative age-related macular degeneration. Forty-seven patients were included in this study. Its findings showed a significant reduction in choroidal volume and choroidal thickness.